Workshop on Digital Marketing and the Utilization of Coconut Waste - Pieter Putra Syofyan; Yusti Atika (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2026)
This outreach activity aims to enhance the competitiveness of MSMEs in Nagari Koto Baru through digital marketing and the utilization of coconut waste. There are limitations in market reach, and the community’s utilization of coconut waste has not yet been optimized. The methods employed in this activity include workshops and outreach sessions involving MSME operators, featuring guest speakers who are community leaders and business practitioners. This initiative has resulted in improved understanding among SME operators regarding digital marketing. Abundant coconut waste can be developed into economically valuable products. This initiative holds potential for fostering SME development, creating new business opportunities, and supporting environmental conservation